Determination of Controlled Local Hyperthermia and Magnetic Hyperthermia of Cancer Diseases in Skin - Zviad Kovziridze; Paata Khorava; Nunu Mitskevich (Advanced Concepts in Medicine and Medical Research Vol. 5, 2023)
This chapter discusses about controlled Local Hyperthermia and Magnetic Hyperthermia of Surface (Skin) Cancer Diseases. Index of morbidity and lethality conditioned by malignancies in the whole world is increasing permanently. Early diagnostics is rather difficult and majority of patients address hospitals because of generalized cancers, when they need combined surgery, radiation and drug therapy and complex treatment. Average size of hematite and magnetite micro and Nano powders and poly dispersity index, zeta potential and distribution of particles were studied. Analysis showed that average size of the obtained particles for magnetite is 740.9 nm, for hematite particles 30 - 35 nm. Alternate current feed source was created for hyperthermia. Based on the objectives’ requirements, U-type Mn Zn material magneto conductors were chosen. Glass test tubes containing magnetite or hematite suspensions were inserted into gaps that were cut to 10.0 and 8.0 mm in width. A series of experiments conducted at different frequencies and field intensities revealed that a more potent device with a frequency of up to 10 megahertz was required for effective magnetic hyperthermia therapy in order to reach the temperature of 43\(^°\)-45\(^°\)C, which is required for the full activation of Neel and Brown mechanisms in particles. At the next stage, on the basis of experimental material the anti- cancer mono-therapeutic effect of hyperthermia and its adjuvant action in poly chemotherapeutic treatment was presented by the use of a device created by us “LEZI”. Results of visual observations are proved for all three animals, on the basis of measurements made after three, seven and ten sessions. As a result of the experiment it was shown that in all animals (outbred albino mice, 3 months old) inhibition of cancer growth was fixed and intra tumor necrosis was developed, while after 7 and 10 sessions tumors were ulcerated, which refers to positive effect of the experiment (Conclusion of Pathologic anatomical Laboratory “PATGEO”, Tbilisi, Georgia).